"I Want to Help" versus "I Am Just Mad": How Affective Commitment Influences Customer Feedback Decisions. (May 2015) - Liu, Stephanie Qing; Mattila, Anna S.
This study investigates the joint effects of affective commitment, feedback valence, and feedback use on customers' willingness to give feedback following a service failure. Our findings reveal that customers who have high levels of affective commitment to a service firm exhibit both a strong motivation to help a firm improve its business and a great need to maintain positive relationships with the firm's frontline employees. Therefore, affectively committed customers are more willing to help the firm by lodging complaints when such feedback is not used for employee evaluation purposes. In addition, driven by their strong motivation to help the firm, affectively committed customers are more willing to offer constructive suggestions than their counterparts with low levels of emotional attachment.